Atmospheric Corrosion Analysis and Rust Evolution Research of Q235 Carbon Steel at Different Exposure Stages in Chengdu Atmospheric Environment of China. (26th February 2020) - Wang, Zhigao; Wang, Mei; Jiang, Jie; Lan, Xinsheng; Wang, Fangqiang; Geng, Zhi; Tian, Qianqian
Abstract : In order to effectively reduce and retard corrosion of the power transmission and transformation equipment in Chengdu power grid and to improve power supply reliability, Q235 carbon steel material which is the most widely used metal material in power grid was selected as the targeted research object in this article. Exposure experiments were performed in urban atmospheric environment of Chengdu city in the southwest region of China. The corrosion behavior of Q235 carbon steel material was investigated at different seasons. The macro- and micromorphologies after corrosion were observed using a digital camera and scanning electron microscopy (SEM), respectively. Element distribution of the rust layer and the corrosion products was characterized by energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR); the corrosion mechanism was also briefly analyzed.